Clear approach: peer-led approaches in Youth Offender Institutions - Andrew Brierley (Scottish Journal of Residential Child Care)
This article undertakes an analysis of His Majesty’s Inspectorate of Prisons’ (HMIP) inspection reports of Young Offender Institutions (YOIs) in England over a 20-year period. The analysis is synthesised with the author’s lived experience of being both an incarcerated child in YOI and a professional working with children in custody. The analysis was instigated by a letter written by the Independent Monitoring Board (IMB) to the Rt Hon Damian Hinds, Minister of State for Justice, indicating that the current state of affairs in England’s YOIs is ‘positively inhumane.’ The current article argues that YOIs have never been ‘positively humane’, having always fallen short of ‘improving outcomes for children’, through the lens of recidivism. The author argues that YOIs also overlook peer-led programmes to promote children desisting from offending, through illuminating a growing body of evidence which suggests this approach can provide ‘hooks for change’ for children to desist from crime, and that it presents a model of good practice that could be used as a child first approach.